2001
DOI: 10.1016/s0008-6363(00)00312-6
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid regulates proliferation, migration, differentiation, and extracellular matrix turnover of human arterial smooth muscle cells

Abstract: atRA was found to be a potent inhibitor of both haSMC-proliferation and -migration, even in coculture with haEC releasing growth factors. In addition, redifferentiation, ECM synthesis and ECM degradation were regulated by atRA which also influence haSMC migration and intima formation. Thus, atRA-treatment seems to be a promising strategy for the inhibition of processes involved both in atherosclerosis and restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…We previously showed that atRA decreases the expression of smooth muscle ␣-actin in intimal SMCs. 9 In contrast, other investigators found that atRA increases the expression of both smooth muscle ␣-actin and smooth muscle myosin heavy chain 43,44 in SMCs from the medial layer of the vessel. This suggests that the differentiation state of the SMC influences the effects of atRA on the expression of contractile proteins.…”
Section: Discussionmentioning
confidence: 85%
“…We previously showed that atRA decreases the expression of smooth muscle ␣-actin in intimal SMCs. 9 In contrast, other investigators found that atRA increases the expression of both smooth muscle ␣-actin and smooth muscle myosin heavy chain 43,44 in SMCs from the medial layer of the vessel. This suggests that the differentiation state of the SMC influences the effects of atRA on the expression of contractile proteins.…”
Section: Discussionmentioning
confidence: 85%
“…ATRA typically inhibits 50-90% of aortic or pulmonary SMC proliferation induced by growth factors (8,10,11,13,23). We tested the hypothesis that ATRA may also inhibit the proliferation of airway SMCs.…”
Section: Effects Of Atra On Airway Smc Proliferation and Apoptosismentioning
confidence: 99%
“…ATRA inhibits PDGF-induced proliferation and induces apoptosis in rat and human aortic SMCs (11)(12)(13). In cultured pulmonary artery SMCs, ATRA inhibits serotonin-induced proliferation (8).…”
mentioning
confidence: 99%
“…Incubation of multipotential P19 embryonal carcinoma cells with retinoids induces differentiation of VSMCs through the induction of α-smooth muscle actin (28,29). Moreover, RA inhibits the production of several matrix metalloproteinases, and this inhibition may suppress the migration of VSMCs (30,31). Neointima formation after endothelial injury has also been shown to be inhibited by RA treatment in vivo (27,32,33).…”
Section: Discussionmentioning
confidence: 99%